Экспериментальное исследование влияния пространственного расположения датчиков магнитного поля на эффективность замкнутой системы активного экранирования магнитного поля линий электропередачи - Кузнецов, Б.И.; Никитина, Т.Б.; Волошко, А.В; Бовдуй, И.В; Виниченко, Е.В.; Кобылянский, Б.Б. (Електротехніка і електромеханіка, 2017)
Проведено экспериментальное исследование влияния пространственного расположения датчиков магнитного поля
на эффективность замкнутой системы активного экранирования магнитного поля линий электропередачи на разработанном макете трехфазной одноцепной воздушной линии электропередачи, создающей вращающееся поле с наиболее сложной пространственно-временной структурой. Экспериментально показано, что наибольшую эффективность имеет замкнутая система активного экранирования магнитного поля, у которой датчики магнитного поля
пространственно расположены в расчетных точках, полученных при синтезе системы, в которых значения соответствующих компонент вектора магнитной индукции принимают минимальное значение Проведено експериментальне дослідження впливу просторового розташування датчиків магнітного поля на ефективність замкнутої системи активного екранування магнітного поля ліній електропередачі на розробленому макеті
трифазної одноланцюгової повітряної лінії електропередачі, яка створює обертове поле з найбільш складною просторово-часовою структурою. Експериментально показано, що найбільшу ефективність має замкнута система активного екранування магнітного поля, у якій датчики магнітного поля просторово розташовані в розрахункових точках,
отриманих при синтезі системи, в яких значення відповідних компонент вектора магнітної індукції приймають мінімальне значення. Purpose. Experimental research of magnetic field sensors spatial arrangement influence on efficiency of closed loop active
screening system by magnetic field of high voltage power lines
developed a three-phase single-circuit high voltage power lines,
creating a rotating magnetic field with the most complex spacetime structure. Methodology. Optimal spatial arrangement of
the magnetic field sensors is determined by solving the active
magnetic field screening system synthesis problems with which
the system provides the greatest efficiency of the active magnetic
field shielding. Synthesis of active screening system is reduced
to the problem of multi-criteria nonlinear programming with
constraints in which calculation of the objective functions and
constraints are carried out on the basis of Biot-Savart-Laplace
law. The problem is solved by a stochastic multi-agent optimization by multiswarm of particles which can significantly reduce
the time to solve it. Calculated arrangement of magnetic field
sensors in a given space defined by the points at which the values of the corresponding components of the vector of magnetic
induction take minimal values. Results. For the first time experimentally that changes in the position of the magnetic field
sensors relative to their calculated position reduces the effectiveness of screening. The optimum position of the magnetic
field sensors are the points at which the levels of the magnetic
induction vector of projections orthogonal to the planes of the
compensating coils are minimum values. Originality. For the
first time invited to place sensors closed loop active screening
system by magnetic field of high voltage power lines at the
points where the calculated levels of corresponding projections
of the magnetic induction vector orthogonal planes compensating windings are minimum values. Practical value. Practical
recommendations for evidence-based selection of the spatial arrangement of the magnetic field sensors in a given area to ensure maximum efficiency of the active magnetic field screening
system